Saskatchewan Joins British Columbia in Introducing an Immunize or Mask Policy - Amy Zarzeczny (McMaster University Library Press, 2015)
Seasonal influenza is a contagious respiratory infection for which certain populations, particularly seniors in long-term care and medically vulnerable individuals receiving care as in-patients in health care facilities, are at heightened risk for serious complications. Accordingly, annual influenza vaccination is a public health objective. In September 2014, Saskatchewan joined British Columbia and became the second Canadian province to implement a so-called "immunize or mask" policy that applies to individuals in patient care locations including, but not limited to, health care workers. The policy is focused on promoting patient safety by reducing the transmission of influenza in regional health authority facilities. On its face, this policy aligns well with the Ministry of Health's commitments to patient-centered care, to quality improvement, and to thinking and acting as one system. The policy will be adopted and implemented by each of the 13 regional health authorities and the single cancer agency in the province. Preliminary evaluation is anticipated after this first year of policy implementation.